Total pancreatectomy and islet cell autotransplantation: a 10-year update on outcomes and assessment of long-term durability. Issue 11 (November 2022) - Turner, Kevin M.; Delman, Aaron M.; Donovan, Eileen C.; Brunner, John; Wahab, Shaun A.; Dai, Yufei; Choe, Kyuran A.; Smith, Milton T.; Patel, Sameer H.; Ahmad, Syed A.; Wilson, Gregory C.
Abstract: Background: Total pancreatectomy and islet cell autotransplantation (TPIAT) offers an effective, lasting solution for the management of chronic pancreatitis up to 5-years post-operatively. Our aim was to assess durability of TPIAT at 10-years. Methods: Patients undergoing TPIAT for chronic pancreatitis eligible for 10-year follow-up were included. Primary outcomes, including endocrine function and narcotic requirements, were reported at 5-, 7.5-, and 10-years post-operatively. Results: Of the 231 patients who underwent TPIAT, 142 met inclusion criteria. All patients underwent successful TPIAT with an average of 5680.3 islet equivalents per body weight. While insulin independence tended to decrease over time (25.7% vs. 16.0% vs. 10.9%, p = 0.11) with an increase in HbA1C (7.6% vs. 8.2% vs. 8.4%, p = 0.09), partial islet function persisted (64.9% vs. 68.0% vs. 67.4%, p = 0.93). Opioid independence was achieved and remained durable in the majority (73.3% vs. 72.2% vs. 75.5%, p = 0.93). Quality of life improvements persisted, with 85% reporting improvement from baseline at 10-years. Estimated median overall survival was 202.7 months. Conclusion: This study represents one of the largest series reporting on long-term outcomes after TPIAT, demonstrating excellent long-term pain control and durable improvements in quality of life. Islet cell function declines over time however stable glycemic control is maintained. Graphical abstract: Image 1